Rapid detection of Streptococcus pyogenes’ antigens in patients of 0 to 14 years of age, assisted in two pediatric emergency wards (2/14/2018-4/13/2018) (Archives of Pediatrics of Uruguay, 2023)
Introduction: streptococcal infections can show fever, pharyngotonsillar inflammation with or without swabs, palatal petechiae, cervical adenitis, scarlatiniform rash and/or abdominal pain. Rapid detection tests for S. pyogenes antigens (DRASP) with high specificity and somewhat lower sensitivity are a useful at the Emergency Ward.Objectives: know the usefulness of a DRASP test in 2 Pediatric Emergency, describe the clinical and epidemiological characteristics of the patients studied during the research period and its correlation with the culture of pharyngeal exudates by calculating sensitivity (S) , specificity (S), positive predictive value (PPV), and negative predictive value (NPV).Material and Methods: prospective, observational, cross-sectional study carried out in two pediatric emergency wards. We included children who underwent DRASP and pharyngeal swab (PS) between February 14 and April 13, 2018. The following data were recorded: sex, age, reason for consultation, diagnosis, treatment, destination, test results and throat cultures. S, S, PPV and NPV were calculated.Results: n=241 children. Range 8 months - 14 years, average 6 years. 103 children (42.7%) consulted due to fever; 48 due to sore throat, 11 due to rash and 47 due to other symptoms. 95% of children were discharged. DRASP negative 87.6% (N: 211) and positive 12.9% (N: 31). Negative EP 80.1% (n: 193) and positive for SβHGA in 13.7% (n: 33). The test sensitivity was 52% and specificity 93%. The PPV 55% and the negative 92%. The most frequent diagnosis was viral pharyngitis 132 (54.7%).Conclusions: the test was applied mainly to febrile schoolchildren, some with odynophagia. A quick etiology differentiation is helpful, since it prevents antibiotics from being used in the event of a negative result. These results support the use of DRASP in pediatric emergency wards.
Keywords: Streptococcus pyogenes; Pharingitis; Child; Teenager